Application Value of Magnetic Resonance Arthrography of the Shoulder in Nursing and Diagnosis of Patients with Shoulder Joint Injury. (24th August 2021) - Chen, Si; Shi, Yuanyuan; Xue, Pan; Chen, Xue
Abstract : Supraspinatus tendon injury is a common clinical shoulder joint disease and is one of the most common causes of shoulder pain and dysfunction. Supraspinatus tendon injury will lead to articular cartilage injury and degeneration, then cause joint disease, seriously affect the quality of life of patients, and bring a huge burden to the family and society. This paper mainly studies and evaluates the application value of special signs of shoulder joint and indirect MR imaging in the diagnosis of supraspinatus tendon injury. Through a series of special examinations for the diagnosis of supraspinatus tendon injury in 90 patients, including zero degree abduction resistance test, arm drop test, Jobe test, Neer sign, and Hawkins sign, all patients in the study underwent indirect magnetic resonance imaging of the shoulder joint. Finally, arthroscopic examination results were used as the "gold standard" to evaluate and analyze the diagnosis. The results showed that among the special signs, the specificity of the falling-arm test was the highest (72.2%) in the diagnosis of full-thickness supraspinatus tendon injury. Hawkins sign had the highest sensitivity (84.0%). In the diagnosis of partial supraspinatus tendon injury, the specificity of the Jobe test was the highest, which was 66.6%. The Neer sign had the highest sensitivity of 50.0%. In the diagnosis of full-thickness supraspinatus tendon injury, there was no significant difference in sensitivity between indirect MRI and Hawkins sign, but the diagnostic specificity of indirect MRI was higher than that of special sign examination. In the diagnosis of partial supraspinatus tendon injury, the sensitivity and specificity of indirect MR imaging are higher than those of special sign examination.